Peran dan Kedudukan Scientific Crime Investigation dalam Hukum Pembuktian Acara Pidana (Studi Kasus Putusan Nomor 777/Pid.B/2016/PN.Jkt.Pst. dan Putusan Nomor 796/Pid.B/2022/PN Jkt.Sel) - Muin, Irwan; Fakhlur, Fakhlur (FOCUS, 2025)
Scientific Crime Investigation (SCI) is used as a scientific approach in uncovering, investigating, and proving a crime. SCI utilizes technology and forensic science to dig up accurate and objective evidence, especially in cases of complex, obscure, planned crimes, or without direct witnesses. The formulation in this study is how the normative concept of Scientific Crime Investigation is in criminal procedural evidence law and what is the role and position of Scientific Crime Investigation in the practice of criminal case evidence. And the method used in this study is normative juridical, namely a legal research method that focuses on written legal norms, such as laws and regulations, legal doctrines, and court decisions. This method is often referred to as doctrinal research, because it aims to find the principles, concepts, and applicable legal rules. The results of the study show that Scientific Crime Investigation (SCI) is a method of investigation and inquiry that emphasizes a scientific approach by utilizing forensic science and technology—such as digital forensics, DNA, ballistics, and forensic medicine—to reveal the material truth of a crime. This approach is very appropriate and effective, especially for uncovering crimes that are carried out in secret, planned, and without witnesses. SCI produces scientific evidence that is legally valid and has high evidentiary power, both in the investigation process by investigators, prosecution by prosecutors, and in the consideration of judges' decisions in criminal trials, as regulated in Article 184 paragraph (1) of the Criminal Procedure Code.